An overview of available drugs for management of opioid abuse during pregnancy. Issue 1 (December 2017) - Laslo, Jillian; Brunner, Jon-Michael; Burns, Daniel; Butler, Emily; Cunningham, Autumn; Killpack, Ryan; Pyeritz, Courtney; Rinard, Kimberly; Childers, Jennifer; Horzempa, Joseph
Abstract The prevalence of opioid abuse in the United States has been steadily increasing over the last several years among many major demographics, including pregnant women. Rise in prenatal opioid abuse has resulted in subsequent escalation of neonatal abstinence syndrome incidence, prompting the US Congress to pass the Protecting Our Infants Act of 2015. This act specifically calls for a critical review of current treatment options for prenatal opioid abuse which may ultimately lead to the development of better therapies and a decreased incidence of neonatal abstinence syndrome. Currently, the American College of Obstetricians and Gynecologists recommends methadone, buprenorphine, or buprenorphine/naloxone in the treatment of prenatal opioid abuse. In this review, each maintenance therapy treatment option is discussed and compared revealing inconsistencies in postpartum retention rates, effects on fetal development, and availability to patients due to restrictions in health care coverage. Although each of these treatment options reduces opioid abuse and potential negative outcomes for the fetus, the shortcomings of these drugs highlight the overarching need for an improved standard of care. Drug developers and lawmakers should consider that affordability, coverage by health insurance, and success in retention rates substantially impacts the decision of the patient and healthcare provider regarding utilization of a particular opioid maintenance therapy.